The Financial Lives of the Workers: An Analysis Amid Corona Pandemic in Bangladesh - Shahen, Md. Abu (ABC Journal of Advanced Research, 2022)
This paper has tried to explore the nature of the living patterns of the workers amid the CORONA pandemic in Bangladesh. The article is shaped entirely by qualitative and secondary data based. However, Bangladesh has achieved tremendous success in the readymade garment sector. Readymade garment sectors are altogether dependent on male and female workers who are contributing to the nation as well as to the sectors. Nevertheless, due to the outbreak of the CORONA virus in 2020, Bangladesh is facing a pandemic situation that makes the workers more vulnerable. They are suffering difficulties in many forms, including layoff, closed or reduced remuneration, factory shutdown, congested working settings, prolonged working hours and overtime, unsecured workplace, lack of protective measures, lack of rehabilitating supports, delay of their children’s education, traumatic and fearful environment of worker’s children, and insufficient health facilities for them. Moreover, the pandemic is hampering the activities of apparel workers, and other informal workers such as rickshaws and van pullers, agriculturists, construction laborers, hawkers, rag pickers, transport workers, and part-time domestic employees are all examples of part-time domestic workers. They are the most vulnerable segment of the CORONA pandemic situation in Bangladesh. As a result, they cannot afford the necessities of family members, including daily food, education, nutrition, and health, due to low income.